ANALISA PENERAPAN DIRECT ROUTE TERHADAP KESELAMATAN LALU LINTAS UDARA DI PERUM LPPNPI CABANG PEMBANTU PANGKALAN BUN - Farahdina Audri Firstyaningtyas; Laila Rochmawati; Raharjo Tedjo Prasetyo (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In the airspace of Pangkalan Bun TMA there is often traffic to the surrounding airport by applying a direct route. This is often a problem for traffic control officers. When air traffic density occurs at Pangkalan Bun, TMA causes frequent conflicts and indirectly endangers aircraft in Pangkalan Bun airspace. The problem studied in this final project is the analysis of the application of direct routes to air traffic safety at Perum LPPNPI, Pangkalan Bun Sub-Branch. The research method that the author uses is using a questionnaire. Data analysis methods used are quantitative methods and measurements using a Likert scale. To find out more about how far the application of direct routes to air traffic safety at Perum LPPNPI Sub-Branch Pangkalan Bun, the authors distributed questionnaires to 12 respondents at Perum LPPNPI Sub-Branch Pangkalan Bun. From this study, the calculation results obtained a cumulative score of 40.4 from the questionnaire, which stated that the application of direct routes to air traffic safety was not optimal. So, on this occasion the author provides suggestions that can be applied, namely reviewing the Letter of Operational Coordination Agreement between the adjacent units concerned regarding the application of direct routes